2013
DOI: 10.1371/journal.pone.0069797
|View full text |Cite
|
Sign up to set email alerts
|

Isospora suis in an Epithelial Cell Culture System – An In Vitro Model for Sexual Development in Coccidia

Abstract: Coccidian parasites are of major importance in animal production, public health and food safety. The most frequently used representative in basic research on this group is Toxoplasma gondii. Although this parasite is well investigated there is no adequate in vitro model for its sexual development available and knowledge on this important life cycle phase is therefore scarce. The use of Isospora suis , a sister taxon to T. gondii and the causative agent of piglet coccidiosis, could provide a solution for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Piglets were raised with the sow in the animal facilities of the Institute of Parasitology, University of Veterinary Medicine Vienna, Austria. Infection of piglets, oocyst collection, oocyst isolation, oocyst purification and excystation were performed as described previously [7]. In deviation to the original protocol, after NaOCl treatment and washing, the oocysts were vortexed three times for 45 s with Precellys ® glass beads (Peqlab, Erlangen, Germany) in 2% sodium taurocholate hydrate (Sigma-Aldrich, St. Louis, USA) in DMEM/Ham's F-12 culture medium (Gibco, Thermo Fisher Scientific, Waltham, USA).…”
Section: Cystoisospora Suis Oocyst Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piglets were raised with the sow in the animal facilities of the Institute of Parasitology, University of Veterinary Medicine Vienna, Austria. Infection of piglets, oocyst collection, oocyst isolation, oocyst purification and excystation were performed as described previously [7]. In deviation to the original protocol, after NaOCl treatment and washing, the oocysts were vortexed three times for 45 s with Precellys ® glass beads (Peqlab, Erlangen, Germany) in 2% sodium taurocholate hydrate (Sigma-Aldrich, St. Louis, USA) in DMEM/Ham's F-12 culture medium (Gibco, Thermo Fisher Scientific, Waltham, USA).…”
Section: Cystoisospora Suis Oocyst Collectionmentioning
confidence: 99%
“…Previous studies have shown that the development of C. suis in vitro is comparable with the life-cycle in vivo; however, the development of sexual stages in vitro is delayed [7]. This makes it possible to observe, harvest and examine sexual stages in the short time frame in which they occur.…”
Section: Introductionmentioning
confidence: 99%
“…Like other Cystoisospora species, C. suis entirely develops in one host ( 26 , 27 ) (Figure 1 ). Directly after ingestion, sporulated oocysts undergo excystation and sporozoites invade the small intestine epithelium ( 12 , 28 ) to reproduce within a parasitophorus vacuole ( 29 , 30 ).…”
Section: Cystoisospora – What Do We Really Know About the LImentioning
confidence: 96%
“…An experimental model mimicking the field situation ( 10 ) in conventional piglets gave deeper insight into neonatal porcine cystoisosporosis. This was further strengthened by the establishment of an in vitro culture system supporting the entire lifecycle of C. suis in intestinal porcine epithelial cells ( 26 ). Moreover, gnotobiotic piglets are available as infection models for specific applications ( 3 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…New techniques in biotechnology and bioinformatics have enabled rapid and cost-effective screening of genomes and transcriptomes of parasites for vaccine and drug target candidates (as reviewed in [4, 12], and others) including A. suum [13] , T. suis [14] , T. gondii (www.toxodb.org/) and C. suis (Palmieri, submitted). For C. suis a genome size of 83 Megabases encoding >8300 genes is estimated, and a recently developed pipeline for the search of vaccine candidates in apicomplexan parasites (Vacceed; [10]) has detected 562 candidates in C. suis which now need to be evaluated further in silico, in vitro (using a cell culture system supporting the complete life cycle of C. suis ; [50]) and in vivo .…”
Section: Background - Vaccines Against Parasitesmentioning
confidence: 99%